FAKTOR – FAKTOR FUNDAMENTAL YANG MEMPENGARUHI BETA SAHAM PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI - Yulia Yulia; Hotman T. Pohan (Jurnal Magister Akuntansi Trisakti, 2015)
The objectives of this research are to analyze and investigate whether there is influence from financial leverage, liquidity, assets growth, assets size, return on investment and dividend payout ratio to stock beta. This research uses 309 financial statement of non-financial companies listed in Indonesia Stock Exchange during the period of 2011 to 2013. The result of this research shows that assets size has significant influence to stock beta. On the other hand, financial leverage, liquidity, assets growth, return on investment and dividend payout ratio have no significant influence to stock beta.